PENINGKATAN KETERAMPILAN PEMBELAJARAN AKOMODATIF BAGI GURU DI SEKOLAH INDONESIA JEDDAH - Ashar, S.Pd., M.Ed., Muhammad Nurul; Sujarwanto, Sujarwanto; Riyanto, Yatim; Saroinsong, Wulan Patria; Setiawan, Beni; Budiyanto, Budiyanto; Nur, Devina Rahmadiani Kamaruddin (Universitas Negeri Surabaya, 2025)
Accommodative learning needs to be implemented in schools that have students with disabilities. Teachers at Sekolah Indonesia Jeddah currently lack adequate knowledge and skills in applying accommodative learning strategies. This condition arises due to the absence of specialized programs for enhancing teachers' competencies in accommodative learning and the lack of dissemination of inclusive education guidelines. Therefore, this community service program aims to improve teachers' understanding and skills in accommodative learning while also promoting the guidelines for implementing inclusive education. The program was conducted through offline training sessions using lecture, discussion, and case study methods. The training results indicate an improvement in teachers' understanding and skills, as evidenced by a 35-point increase in post-test scores compared to the pre-test. Evaluation results also show high satisfaction with the training materials, with over 70% of teachers reporting being very satisfied. Furthermore, speaker evaluation results indicate that over 80% of teachers were highly satisfied with the speaker's performance. Nevertheless, follow-up programs are still necessary to ensure that teachers retain and apply the acquired knowledge effectively. Keywords: accommodative learning, inclusive education, teachers